Kritik Sosial dalam Musik Metal: Analisis Semiotika Lagu ‘God Is a Weapon’ Falling in Reverse - Julita Mustika; Marini Marini (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
Enthusiasm for metal music in Indonesia has grown since the 1980s, but to this day this genre is still often perceived negatively because it is synonymous with violence, controversy, and dark aesthetics. As a result, the symbolic meaning and social criticism contained in metal music are often overlooked. This research starts from the main problem of the public's lack of understanding of symbols, meaning construction, and social messages in metal music. Therefore, this study aims to uncover the symbolic meanings constructed through lyrics, visuals, and musical elements in metal genre works. The song "God Is a Weapon" was chosen because it presents religious symbols, power, morality, and a feminine divine figure in a provocative manner, as well as being one of the most popular works of the band with a high level of global popularity, Falling in Reverse, thus having a wide range of meanings in popular culture. The research method used is descriptive qualitative with documentation techniques on official lyrics, music videos, and supporting literature. Data analysis was conducted using Roland Barthes' semiotics through three levels of meaning: denotation, connotation, and myth and its validity was tested through source triangulation. The results of the study indicate three main meaning constructions. First: the representation of religion as power, second: the representation of sin and moral decay, and third: gender relations and feminine divine figures. Overall, this study confirms that God Is a Weapon is a popular cultural text that combines lyrics, visuals, and music to present social critique in contemporary society.